Electrical stunning in South American catfish (Rhamdia quelen) using direct current waveform: welfare and meat quality - Rucinque,Daniel Santiago (2021)
ABSTRACT: In Brazil, humane slaughter regulation is in use since 2000; however it is not applied to fish. This paper studied parameters for electrical stunning using direct current waveform in South American catfish (Rhamdia quelen) and its subsequent effects on muscular pH and rigor mortis. Seventy fish were allocated into two groups. In group 125, fish were stunned using 125 Volts (V), 30 Hz, duty cycle of 90% and 1.3 Amp (A) applied for 30 s; in group 400, fish were stunned with 400 V, 30 Hz, duty cycle of 27%, 0.9 A, for 30 s. Unconsciousness time was determined through behavioural assessment. After slaughter, ten fish from each group were refrigerated for both measurements muscular pH and rigor mortis index (RMI) at 0, 3, 6, 24, 72 and 120 h. In 125, 14.4% (5/35) of fish were not effectively stunned, in contrast with 400 in which 100% of fish (35/35) were effectively stunned. The unconsciousness duration was higher in 400 group (87.7±16.1 s) in contrast with group 125 (66.6 ± 16.1 s). Until 6 h post mortem ninety percent of fish reached maximum rigor mortis (RMI=100%).